2018
DOI: 10.1111/jcpp.12964
|View full text |Cite
|
Sign up to set email alerts
|

Annual Research Review: Developmental computational psychiatry

Abstract: Most psychiatric disorders emerge during childhood and adolescence. This is also a period that coincides with the brain undergoing substantial growth and reorganisation. However, it remains unclear how a heightened vulnerability to psychiatric disorder relates to this brain maturation. Here, we propose 'developmental computational psychiatry' as a framework for linking brain maturation to cognitive development. We argue that through modelling some of the brain's fundamental cognitive computations, and relating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 116 publications
0
46
0
Order By: Relevance
“…Lack of strong age dependency of performance has been observed in other reinforcement learning tasks (e.g. [37] in adolescents vs. adults), but both performance and cognitive parameter age dependencies very much depend on the specific details of the task at hand [39,40]. Practice effects may have affected the improvement in the extent to which people were described by our models.…”
Section: Discussionmentioning
confidence: 74%
“…Lack of strong age dependency of performance has been observed in other reinforcement learning tasks (e.g. [37] in adolescents vs. adults), but both performance and cognitive parameter age dependencies very much depend on the specific details of the task at hand [39,40]. Practice effects may have affected the improvement in the extent to which people were described by our models.…”
Section: Discussionmentioning
confidence: 74%
“…One goal of computational neuroscience is to assess cognitive processes at a single subject level. For example, predicting/explaining clinical symptoms based on computational/neurological cognitive estimates to eventually inform clinical decisions [54,55]. This requires provision of stable and reliable estimates and our study highlights ways this can be advanced.…”
Section: Discussionmentioning
confidence: 99%
“…In a separate study, we used an abbreviated version of the current task and revealed developmental changes in belief updates during adolescence 37 . This can provide a particularly relevant benchmark as the onset of many psychiatric disorders takes place during adolescence 38 . More generally speaking, our study opens the door to broader applications of the tools and models from information sampling to understand social decision-making.…”
Section: Discussionmentioning
confidence: 99%